Pengembangan Karakter Anak Usia Dini Melalui Pembelajaran Model Parenting - Muhammad Yusri Bachtiar; Parwoto Parwoto; Azizah Amal (Seminar Nasional LP2M UNM, 2019)
This study raises the problem (1) What is the level of need for early childhood character development through learning of the parenting model in Al-Hidayah An-Nas Kindergarten Tamamaung, Panakkukang District, Makassar City? (2) How is the prototype of early childhood character development through learning parenting models in Al-Hidayah An-Nas Kindergarten Tamamaung Village Panakkukang District Makassar City? (3) How to analyze the level of validity and practicality of early childhood character development through learning the parenting model in Al-Hidayah An-Nas Kindergarten Tamamaung, Panakkukang District, Makassar City, The research objectives are (1) Describe the level of early childhood character development needs through learning parenting model in Al-Hidayah An-Nas Kindergarten Tamamaung Village Panakkukang District Makassar City. (2) Knowing the prototype of early childhood character development through learning parenting models in Al-Hidayah An-Nas Kindergarten Tamamaung Village Panakkukang District Makassar City. (3) Knowing the analysis of the validity and practicality of early childhood character development through learning the parenting model in Al-Hidayah An-Nas Kindergarten Tamamaung, Panakkukang District, Makassar City. This research method with R&D with ADDIE model, in this study includes three stages of analysis, design and development. The results of the study were obtained (1) The description that basically the teacher has not been optimal in using the parentign model to develop the character of children, where the activity is still centered on the teacher, (2) The description of the needs analysis shows that it is very necessary to have a parenting model to develop the character of children in kindergarten , (3) The description of the results of the development of the model with the validity test on the observation sheet shows valid results and the practical test of learning parenting models in kindergarten empirically shows that the overall implementation is in a very good category and meets the criteria of excellence when testing character development through the parenting learning model takes place in accordance with the character of early childhood.